Morphology Characteristic Study of Adsorbent Prepared from Sidoarjo Hot Mud - Dwi Hery Astuti; Aissyah Lathifah Adriyanti; Arrizal Buditama; Ardika Nurmawati; Lucky Indrati Utami; Sani (Future Science, 2022)
Sidoarjo hot mud has erupted for the past 16 years and has many effects on the environment. This mud contains several porous materials, such as silica and aluminum oxide, which can be used as adsorbents. This study aimed to characterize the morphology of the adsorbent and apply it to waste cooking oil purification. The composition of virgin hot mud was 46.5% SiO2 and 13% Al2O3 with an amorphous crystalline structure. The hot mud was activated with H2SO4 under different drying process conditions where the drying temperature differed from 150oC to 250oC, while the drying period was set from 30 to 90 minutes. After the activation, the structure of the adsorbent became more crystalline. From XRD analysis, the lowest intensity resulted from adsorbent with 225oC and 75 minutes of drying, with 191,038 m2/gr on pore surface area. This adsorbent had a greater pore surface area and gave the best adsorption process.